2006
DOI: 10.1097/01.bpb.0000188251.24771.c9
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of diagnostic delays in slipped capital femoral epiphysis

Abstract: Delay in diagnosis of slipped capital femoral epiphysis has important implications with regard to slip severity and long-term hip outcomes. The aims of this review were to identify the incidence of delayed diagnosis of slipped capital femoral epiphysis in the hospital to which the authors are affiliated, and the causes for such delays. A retrospective review was conducted of all patients admitted to the Women's and Children's Hospital in Adelaide between January 1997 and October 2004 with a diagnosis of slippe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 16 publications
1
37
0
2
Order By: Relevance
“…14 Once the diagnosis is made, treatment is indicated to prevent slip progression. [15][16][17] The goals of treatment for any SCFE or to stop progression of the SCFE, avoid complications (chondrolysis, AVN, SCFE progression, fixation problems), and realignment if/when to improve hip motion and potentially postpone the development of degenerative hip arthrosis. There are multiple treatment options, each having specific advantages and disadvantages.…”
mentioning
confidence: 99%
“…14 Once the diagnosis is made, treatment is indicated to prevent slip progression. [15][16][17] The goals of treatment for any SCFE or to stop progression of the SCFE, avoid complications (chondrolysis, AVN, SCFE progression, fixation problems), and realignment if/when to improve hip motion and potentially postpone the development of degenerative hip arthrosis. There are multiple treatment options, each having specific advantages and disadvantages.…”
mentioning
confidence: 99%
“…Emergency physicians must promptly identify patients with a SCFE, as delays in this diagnosis are associated with increased slip severity and morbidity [1]. Unfortunately, plain radiography including an antero-posterior pelvis view and a frog-leg lateral hip view has a poor overall sensitivity, ranging from 40 to 79% [2].…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, EM physicians were less likely than orthopedic surgeons to request an ED consultation for a hip dislocation; this could result in avascular necrosis, which can have long-term negative effects for a patient. [2][3][4][5] The authors also noted a significant difference between years in training regarding recognizing the need for an urgent orthopedic consult. The results showed that pediatricians' and EM physicians' ability to assess the proper level of urgency for an orthopedic consultation increased as they accumulated years of residency.…”
mentioning
confidence: 95%
“…1 Neglecting to call for an urgent consultation for particular orthopedic diagnoses can lead to incomplete reduction, missed fractures, malunion, nonunion, avascular necrosis, increased infection rate, or growth disturbances. [2][3][4][5] Understanding the key role of primary care and EM physicians, the authors investigated the decision-making process of orthopedic surgeons, pediatricians, and EM physicians to determine whether these 3 specialties reached different conclusions on the urgency of ED orthopedic consults. The authors also studied whether these decisions varied by year in training, to ascertain if variable or no musculoskeletal education during medical school was made up for during the residency training years.…”
mentioning
confidence: 99%